TEKNOHUMANISTIK-TRANSFORMATIF: PENGORGANISASIAN MATERI DAN PEMBELAJARAN BAGI SISWA KELAS AWAL SEKOLAH DASAR DALAM IMPLEMENTASI KURIKULUM 2013 - Nyoman Sri Mulyani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Education is the process of humanizing mankind, in terms of optimization thedevelopment human dignity in a structured and purposeful. That means, education should takeplace in the community, and allow the natural cultural transformation from one generation tothe next generation. The main issues found in this case, that educational institutions have notbeen able to create a superior human with high intellectual ability and reasoning power andalso independent, so that they are able to estimate changes and the development of the worldsociety in the future, particularly with regard to the implications of science and technology topeople's lives. Transformative education is educational process accessing the changes but stillgrounded at the basic values embodied in the nation's outlook on life that is called IdeologyPancasila and the great values of the local cultur. Through the Technohumanistic-transformativeapproach, students learn in the context of real experience, which includes the application ofthinking skills, problem solving, cultural appreciation, and accurate decision-making skills tocausal relationship of science technology and society. The material organization and presentationof technohumanistic-transformative approaches provides an optimal opportunity for teachersto develop and train the thinking skills of the learners, thus it directly impacts improvisation ofthe learning achievement attained by the students in empowering curriculum 2013implementation.